Fatigue Strength of Bridge Girders with Corrugated Web - Emme, Alice; Svensson, Elsa (My University, 2024)
Corrugated steel web girders are emerging as a potential choice for bridge construction due to their material-saving advantages. Fatigue frequently causes failure in constructions subjected to cyclic loading, such as bridges. However, thus far, the Eurocode has not addressed the fatigue strength of bridge girders with corrugated webs, particularly the welding detail between the web and the flange. This thesis thereby investigates the fatigue life of the flange-to-web weld detail in these girders, employing local approaches such as structural hot-spot stress and effective notch stress method. The objective is to compare the results obtained from these local approaches with those derived from the nominal stress method. Subsequently, a fatigue strength class is recommended for each design approach. Moreover, the effect of various corrugation parameters such as the corrugation angle and bending radius on the fatigue life of corrugated web girders have been examined. The Master’s thesis began by collecting data from previous fatigue experiments conducted on corrugated web girders. Specimens identical to the experiment have been modelled in Abaqus for a numerical analysis investigating the nominal-, structural hot-spot- and effective notch stress for all specimens. To simulate the structural behaviour of the experimental girders, a mesh convergence and validation study have been performed separately on each of the specimens. The FE modelling has been described and further results derived. Based on the results of the numerical analysis the nominal-, structural hot-spot- and effective notch stresses have been compared against each other. Concluding that a decrease in the scatter appears when using structural hot-spot stress compared to the nominal stress method. However, looking at the effective notch stress the scatter increased again. Further, a proposal of the detail category for each stress method has been presented. Lastly, the geometric parameters including corrugation angle and bending radius, have been analyzed. Based on the results, the conclusion was that the corrugation angle’s geometrical effects are more considerable compared to the bending radius.
Keywords: Corrugated web, Fatigue, Fatigue life, Nominal stress, Structural hot-spot stress, Effective notch stress, Corrugation angle, Bending radius